Second-generation ethanol: concept, production and challenges - Medeiros, Pedro Vinícius Costa; Theophilo, Paulo Henrique Medeiros; Lopes, Gisele Simone; Ribeiro, Lívia Paulia Dias (Eclética Química, 2023)
The use of biological agents for the large-scale production of biofuels has stood out as successful processes for the advancement of science in the world. The growing exploitation of biomass in the agricultural sector and the emergence of new energy sources generated from food industry waste have become attractive and viable due to the potential and variety of possibilities for using different sources of biomass. The present review was carried out through careful bibliographical research in the literature and in scientific journals for the current discussion of concepts, production methodologies and challenges for the energy sector considering second-generation ethanol (2G ethanol). Several 2G ethanol production methodologies have been implemented as a potential low-cost alternative energy production that follows the principles of Green Chemistry.